2020. Disinfection of Needle-less Connectors Using UVC Light. (15th December 2022) - Rasooly, Julia; Banaei, Niaz; Fourkas, Michael; Schears, Gregory
Abstract: Background: Nearly 50% of post-insertion catheter-related infections are due to microbial ingress from needleless connectors (NC), widely used devices which connect to the end of catheters or infusion sets and enable access for injection of medications and attachment of infusions. Infections arising from NC could result in central line associated bloodstream infection (CLABSI). The clinical guideline for disinfecting NC is to wipe the hub of the NC with a 70% alcohol and to manually scrub the connector surface for at least 15 seconds. Unfortunately, multiple studies have found low compliance with the 15 second disinfection scrub. Methods: In this study, we investigated the efficacy of 1 second of ultraviolet light-C exposure in the reduction of the 3 most common CLABSI associated organisms: Staphylococcus aureus, Candida albicans, Candida auris, and Methicillin-resistant Staphylococcus aureus (MRSA). We tested a total of 30 NC samples for each organism with 3 positive controls and 1 negative control. Results: The log reductions were 5.68, 5.05, 4.41, and 6.38 for S. aureus, C. albicans, C. auris and MRSA, respectively. Growth of Candida albicans with and without UV-C exposure for 1 second. The figure shows the observed growth of Candida albicans from the surface of the connector with and without UV-C exposure for 1 second, displaying no growth on the agar plate for samples that were exposed to 1 second of UV-C disinfection. Log reduction of tested organisms after exposure of UV-C for 1 second. Table 1 displays the overall log reduction of tested organisms after 1 second of UV-C exposure. The results are shown for positive control concentration and log reduction for the test organisms Staphylococcus aureus, Candida albicans, Candida auras, and Methicillin-resistant Staphylococcus aureus. Conclusion: Our findings demonstrate greater than 4 log reduction of common CLABSI-associated organisms with 1 second of UV-C exposure, which we believe would decrease CLABSI rates, increase aseptic technique compliance, and reduce disruption in hospital workflow. Disclosures: Julia Rasooly, MS, Puracath Medical, Inc: Board Member|Puracath Medical, Inc: Stocks/Bonds Michael Fourkas, MS, Puracath Medical, Inc: Grant/Research Support Gregory Schears, MD, Puracath Medical, Inc: Advisor/Consultant|Puracath Medical, Inc: Stocks/Bonds.